INFLUENCE OF INCLUSIVE AND SEGREGATIVE PHYSICAL EDUCATION FOR SCHOOLCHILDREN OF DIFFERENT MEDICAL GROUPS - Bodnar, Ivanna; Pavlova, Iuliia; Sirenko, Romana; Lapychak, Ihor (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The study aimed to compare the effectiveness of inclusive and segregative physical education classes for students of various medical groups, taking into account sociopsychological indicators and indicators of psychoemotional state. The study involved 1,414 schoolchildren aged 10–16 years (M=12.7, SD=1.6). Through the survey, pupils’ wellbeing, needs, motivations, and motor preferences at their leisure and physical education classes, level of situational and personal anxiety, degree of integration of the group, and motivation for success were ascertained. Data comparisons were made between schoolchildren who studied in segregated and inclusive ways of organizing physical education in schools. Attitudes towards schoolchildren’s physical education and leisure patterns make it possible to assert that an inclusive model is effective. Integrative physical education classes are less mentally traumatic, more convenient, and psychologically comfortable than segregative ones. The way physical education is organized does not affect the level of anxiety and the class’s degree of motivation in achieving success in schoolchildren’s activities. Positive changes in the integrative conditions in the mental state come with all schoolchildren, but they are most noticeable among schoolchildren with low functional reserve capabilities.